17β-estradiol mitigates the inhibition of SH-SY5Y cell differentiation through WNT1 expression - Shakya, Rubina; Amonruttanapun, Prateep; Limboonreung, Tanapol; Chongthammakun, Sukumal (My University, 2023)
17β-estradiol (E2) and canonical WNT-signaling represent crucial regulatory pathways for microtubule dynamics and synaptic formation. However, it is unclear yet whether E2-induced canonical WNT ligands have significant impact on neurogenic repair under inflammatory condition. In this study, first, we prepared the chronic activated-microglial-conditioned media, known to be comprised of neuro-inflammatory components. Long term exposure of microglial conditioned media to SH-SY5Y cells showed a negative impact on differentiation markers, microtubule associated protein-2 (MAP2) and synaptophysin (SYP), which was successfully rescued by pre and co-treatment of 10 nM 17β-estradiol. The inhibition of estrogen receptors, ERα and ERβ significantly blocked the E2-mediated recovery in the expression of differentiation marker, SYP. Furthermore, the inflammatory inhibition of canonical signaling ligand, WNT1 was also found to be rescued by E2. To our surprise, E2 was unable to replicate this success with β-catenin, which is considered to be the intracellular transducer of canonical WNT signaling. However, WNT antagonist - Dkk1 blocked the E2-mediated recovery in the expression of the differentiation marker, MAP2. Therefore, our data suggests that E2-mediated recovery in SH-SY5Y differentiation follows a divergent pathway from the conventional canonical WNT signaling pathway, which seems to regulate microtubule stability without the involvement of β-catenin. This mechanism provides fresh insight into how estradiol contributes to the restoration of differentiation marker proteins in the context of chronic neuroinflammation.
Keywords: 17β-estradiol; Canonical WNT; Neuroinflammation; Neuronal differentiation